Pembiasaan Perilaku Cinta Tanah Air Sebagai Bentuk Wawasan Kebangsaan Di Paud IT Attoyyibah - Amanda Aprilia; Syifa Fauziah (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
Early childhood education plays a strategic role in instilling character values, including patriotism as the foundation for national awareness formation. At the early childhood stage, children are in the initial phase of forming attitudes and social identities, so instilling national values needs to be done thru an approach that aligns with the developmental characteristics of children. The issue underlying this research is the need for a deeper understanding of how the process of habituating patriotic behavior is applied in children's daily activities, as well as the role of teachers and the school environment in supporting the formation of national awareness. Therefore, this research aims to describe the process of habituating patriotic behavior and the role of teachers in instilling national values in early childhood at PAUD IT Attoyyibah. This study uses a qualitative approach with a descriptive research type. The subjects of the research include the administrators and teachers of PAUD IT Attoyyibah. Data were collected thru observation, interviews, and documentation, then analyzed using qualitative data analysis techniques that include data reduction, data presentation, and conclusion drawing.The research results show that the habituation of patriotic behavior is implemented integratively in children's learning routines and daily activities, such as lining up orderly, recognizing national symbols, participating in thematic national activities, collaborating in groups, and the exemplary behavior of teachers. Teachers play the role of role models, habit designers, facilitators, guides, reinforcers, mediators of national values, and evaluators of children's behavioral development. The conclusion of this research shows that the consistent, meaningful, and teacher-supported practice of patriotism is effective in fostering a sense of nationalism in early childhood. It is recommended that early childhood education institutions continue to strengthen the habituation of national values thru collaboration with parents and the development of sustainable and contextual programs.